Proteomic Analysis Reveals a Predominant NFE2L2 (NRF2) Signature in Canonical Pathway and Upstream Regulator Analysis of Leishmania-Infected Macrophages - de Menezes, Juliana Perrone Bezerra; Khouri, Ricardo; Oliveira, Camila Victoria Sousa; Petersen, Antonio Luis de Oliveira Almeida; de Almeida, Tais Fontoura; Mendes, Flávia R. L.; Rebouças, Amanda do Amor Divino; Lorentz, Amanda Lopes; Luz, Nívea Farias; Lima, Jonilson Berlink; Ramos, Pablo Ivan Pereira; Soares, Rodrigo Pedro; et al. (Frontiers in Immunology, 2019)
CBA macrophages (MØ) control infection by Leishmania major and are susceptive to Leishmania amazonensis, suggesting that both parasite species induce distinct responses that play important roles in infection outcome. To evaluate the MØ responses to infection arising from these two Leishmania species, a proteomic study using a MudPIT approach with liquid chromatography tandem mass spectrometry (LC-MS/MS) was carried out on CBA bone-marrow MØ (BMMØ). Following SEQUEST analysis, which revealed 2,838 proteins detected in BMMØ, data mining approach found six proteins significantly associated with the tested conditions. To investigate their biological significance, enrichment analysis was performed using Ingenuity Pathway Analysis (IPA). A three steps IPA approach revealed 4 CP and 7 Upstream Transcriptional Factors (UTFs) strongly associated with the infection process. NRF2 signatures were present in both CPs and UTFs pathways. Proteins involved in iron metabolism, such as heme oxigenase 1 (HO-1) and ferritin besides sequestosome (SQSMT1 or p62) were found in the NRF2 CPs and the NRF2 UTFs. Differences in the involvement of iron metabolism pathway in Leishmania infection was revealed by the presence of HO-1 and ferritin. Noteworty, HO-1 was strongly associated with L. amazonensis infection, while ferritin was regulated by both species. As expected, higher HO-1 and p62 expressions were validated in L. amazonensis-infected BMMØ, in addition to decreased expression of ferritin and nitric oxide production. Moreover, BMMØ incubated with L. amazonensis LPG also expressed higher levels of HO-1 in comparison to those stimulated with L. major LPG. In addition, L. amazonensis-induced uptake of holoTf was higher than that induced by L. major in BMMØ, and holoTf was also detected at higher levels in vacuoles induced by L. amazonensis. Taken together, these findings indicate that NRF2 pathway activation and increased HO-1 production, together with higher levels of holoTf uptake, may promote permissiveness to L. amazonensis infection. In this context, differences in protein signatures triggered in the host by L. amazonensis and L. major infection could drive the outcomes in distinct clinical forms of leishmaniasis.